2022
DOI: 10.21203/rs.3.rs-1963208/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Team cohesiveness and efficacy explained outcomes in interprofessional education

Abstract: Background While team cohesiveness and collective efficacy have been construed as important characteristics of a high functioning team, the psychological mechanism through which they promote positive outcomes remains unknown. Yet this mechanism is important to teachers and programme implementers to yield actionable intervention that can be used to craft effective practices for optimizing team outcomes. This is especially true in interprofessional education (IPE) in medical education, where team-based approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Furthermore, other studies from diverse regions across the globe consistently reveal comparable results [14,[45][46][47]. In a 2023 study conducted in Hong Kong, however, males showed higher rates of SAD than females; this contradicts results from other studies and can be explained by the acknowledged sampling size bias within the dataset, as the female sample was significantly larger than the male sample [48]. We can understand the higher frequency of SAD in women most effectively through a vulnerability-stress perspective.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, other studies from diverse regions across the globe consistently reveal comparable results [14,[45][46][47]. In a 2023 study conducted in Hong Kong, however, males showed higher rates of SAD than females; this contradicts results from other studies and can be explained by the acknowledged sampling size bias within the dataset, as the female sample was significantly larger than the male sample [48]. We can understand the higher frequency of SAD in women most effectively through a vulnerability-stress perspective.…”
Section: Discussionmentioning
confidence: 81%
“…Responses are captured on a 5-point Likert scale from 0 (not at all) to 4 (extremely), allowing for a comprehensive symptom severity score ranging from 0 to 68. The scoring system classifies severity into five categories: none or very mild (less than 20), mild (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), moderate (31)(32)(33)(34)(35)(36)(37)(38)(39)(40), severe (41)(42)(43)(44)(45)(46)(47)(48)(49)(50), and very severe (51 or more), enabling detailed analysis of social anxiety levels among the surveyed population.…”
Section: Participants and Surveymentioning
confidence: 99%
“…he role of team cohesion in success is a critical aspect of organizational and group performance. Team cohesion refers to the degree to which team members are connected and motivated to achieve common goals (1,2). This literature review aims to explore the role of team cohesion from a psychological perspective, drawing on various theoretical frameworks and empirical evidence to provide a comprehensive understanding of its impact on success.…”
Section: Introductionmentioning
confidence: 99%
“…Their study emphasized the moderating role of psychological safety in the communication-cohesion relationship, underscoring the importance of creating a psychologically safe environment for effective team dynamics(49).In the context of interprofessional education and healthcare, Ganotice et al (2022) emphasized the importance of team cohesiveness and collective efficacy in promoting positive collaboration outcomes. Their study highlighted the significance of collective efficacy in fostering effective teamwork and collaboration in healthcare settings(2).In the field of organizational management, Yu et al (2022) highlighted the importance of communication openness and its mediating role in nosocomial infection reporting. Their study underscored the significance of open communication in promoting team cohesion and performance in healthcare settings(52).In the context of service management teams, Guchait et al (2014) emphasized the influence of transactive memory systems and psychological safety on the effectiveness of service management teams.…”
mentioning
confidence: 99%